The Illusion of Return : A novel by Samir El-Youssef - Samir El-Youssef (London; Halban Publishers, 2007)
After 17 years, the narrator and his friend, Ali, meet at Heathrow and slowly remember their past in Lebanon. Their memories are concentrated on one fatal night when they were with two other friends for the last time, before tragedy struck. But for the narrator, a personal tragedy had occurred much earlier¿ Both the narrator and Ali are Palestinians born in Lebanon. Like many others, they had to leave in the mid-1980s, when it became a battleground for local armies - Ali to America, the narrator to London. But this is not just a story about suffering, it is also about absurd politics and violence - about a world where tragedy and comedy co-exist. A poignant story that lingers long after one has finished it.
English
Keywords: Palestine; PN3311-3503 Literature (General)- Prose. Prose Fiction